2012
DOI: 10.1152/japplphysiol.00415.2012
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress and anaerobic energy release, but blunted Thr172-AMPKα phosphorylation, in response to sprint exercise in severe acute hypoxia in humans

Abstract: -AMPactivated protein kinase (AMPK) is a major mediator of the exercise response and a molecular target to improve insulin sensitivity. To determine if the anaerobic component of the exercise response, which is exaggerated when sprint is performed in severe acute hypoxia, influences sprint exercise-elicited Thr 172 -AMPK␣ phosphorylation, 10 volunteers performed a single 30-s sprint (Wingate test) in normoxia and in severe acute hypoxia (inspired PO2: 75 mmHg). Vastus lateralis muscle biopsies were obtained be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 68 publications
9
95
3
Order By: Relevance
“…It is interesting to note that, contrary to this study (where muscle antioxidant defense was decreased and muscle hypertrophy was optimized), other studies evaluating the impact of antioxidants in humans (through vitamin E and C supplementation) were shown to impair muscle hypertrophy response and cell signaling leading to muscle hypertrophy[45,46]. Several studies have observed that RT increases hypoxia, metabolite accumulation and ROS production, which seems to be strictly related[22,23,51,52]. In this context, we can hypothesize that RT with moderate/high repetitions and short rest intervals can be a stimulus to produce ROS.…”
Section: Resistance Trainingmentioning
confidence: 61%
“…It is interesting to note that, contrary to this study (where muscle antioxidant defense was decreased and muscle hypertrophy was optimized), other studies evaluating the impact of antioxidants in humans (through vitamin E and C supplementation) were shown to impair muscle hypertrophy response and cell signaling leading to muscle hypertrophy[45,46]. Several studies have observed that RT increases hypoxia, metabolite accumulation and ROS production, which seems to be strictly related[22,23,51,52]. In this context, we can hypothesize that RT with moderate/high repetitions and short rest intervals can be a stimulus to produce ROS.…”
Section: Resistance Trainingmentioning
confidence: 61%
“…The metabolic state of the muscles (as assessed non-invasively via muscle NIRS and blood [Lac - ]) also appeared to be similar in the two F I O 2 conditions, despite lower work produced in hypoxia [18,21]. However, these variables are indirect measures, and other studies have demonstrated greater metabolic perturbations and anaerobic energy release after sprint exercise in hypoxia, suggesting greater peripheral fatigue [19,20,29]. These discrepancies could be due to different measurement techniques and sprint protocols.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have demonstrated greater anaerobic energy release and metabolic perturbations after single-sprint11 and repeated-sprint48 49 exercise in hypoxia. This suggests that sprinting in hypoxia leads to greater and/or earlier metabolic fatigue (and presumably muscle fatigue) than in normoxia.…”
Section: Exercising and Competing At Altitudementioning
confidence: 93%